DAKWAH BIL HIKMAH PERSPEKTIF YUSUF AL -QARADHAWI DALAM RUTINITAS ZIARAH WALISONGO PADA MAJELIS TAKLIM DI DESA KERTASARI - Ahmad Irfan Maulana; Lukmanul Hakim; Dedy Susanto (UIN Sunan Kalijaga, 2024)
The Walisongo pillgrimage is a religious practice that holds significant potential as a contextual and transformative medium for Islamic preaching. This study aims to analyze the implementation of the dakwah bil hikmah concept ftom Yusuf al-Qaradhawi’s perspective within the routine pillgrimage activities conducted by the Majelis Taklim in Kertasari Village. This research employs a qualitative approach using the phenomenological method to explore the meaning and spiritual experiences of the participants. Data were collected through in depth interviews, participatory observation, and documentation and analyzed using thematic analysis. The findings indicate that the pillgrimage serves as an educational and reflective preaching medium. The application of dakwah bil hikmah is reflected in the use of Walisongo’s historical narratives, gentle communication, spiritual dialogues, and the utilization of sacred spaces as non-verbal preaching media. Spiritual reflections during the pillgrimage strengthen both individual spirituality and community social solidarity. The study concludes that culturally based preaching forms an effective, adaptive, and sustainable model of dakwah bil hikmah.